Multidisciplinary Perspectives on a Video Case of Children Designing and Coding for Robotics. Issue 3 (3rd July 2017) - Francis, Krista; Bruce, Cathy; Davis, Brent; Drefs, Michelle; Hallowell, David; Hawes, Zachary; McGarvey, Lynn; Moss, Joan; Mulligan, Joanne; Okamoto, Yukari; Sinclair, Nathalie; Whiteley, Walter; et al.
ABSTRACT: Spatial reasoning plays a vital role in choice of and success in science, technology, engineering, and mathematics (STEM) careers, yet the topic is scarce in grade school curricula. We conjecture that this absence may be due to limited knowledge of how spatial reasoning is discussed and engaged across STEM professions. This study aimed to address that gap by asking 19 professionals to comment on a video that documented children's progression through 5 days of building and programming robots. Their written opinions on the skills relevant to their careers demonstrated by the children revealed that spatial thinking and design thinking are central to what they see.